In the blink of an eye - Abu, Eugenia (Ibadan : Spectrum Books ; Channel Islands, U.K. : In association with Safari Books, 2007)
This book is not simply a collection of Euginea Abu's articles. It is the story of her life.
Includes bibliographical references (p. 327-328).
osc 30/05/13
Loans
Keywords: Nigeria -- Social conditions; Women -- Nigeria -- Social conditions